Adaptation Strategies: Labour Education, Climate Crisis and the UK Trade Union Movement - Stuart Tannock (Global Labour Journal, 2024)
A growing number of climate activists and scholars argue that an effective climate movement needs the involvement of the trade union movement, to be able to push forward the radical social transformations required to address the global climate crisis. This article analyses the recent focus on climate adaptation in labour education and action by trade unions in the UK. Climate adaptation is inherently political, and this article analyses the agendas driving the turn to adaptation, the possibilities that adaptation strategies open up, and some of their risks and limitations. Climate adaptation strategies, the article argues, could represent an important step forward for developing effective labour education and action on the climate crisis, but only if these strategies enable unions to mobilize a focus on the root causes of the crisis, agitate for structural change, and attend to the global and not just local concerns of worker, social and climate justice.